Scientific Research Policy for Health in Portugal: I - European and National Environment - Sá Guerreiro, Cátia (2017)
The global debate on scientific research policy for human health has been led by World Health Organisation with important contributions from other stakeholders such as Council on Health Research for Development, the World Bank and the Global Forum for Health Research. Recently it has been dominated by the thematic agendas of major global financiers. There is a growing interest worldwide in making better use of the evidence resulting from scientific research in health, in the decision-making process regarding health policies, which is fraught with difficulties, as it is the case in Europe. After more than 40 years of democracy and 30 years of European integration, Portugal has bridged the research gap it had previously. However, when compared to global and European research policies, Portugal still has a long way to go regarding investment in research and development.